2021
DOI: 10.1111/iwj.13712
|View full text |Cite
|
Sign up to set email alerts
|

Pressure injury prevention practices among medical surgical nurses in a tertiary hospital: An observational and chart audit study

Abstract: Pressure injuries are frequently occurring adverse events in hospitals, negatively impacting patient safety and quality of care. Most pressure injuries are avoidable if effective prevention strategies are used. However, the extent to which various settings influence their use of prevention strategies is unknown. The aim of this study was to describe and compare pressure injury prevention strategies used by medical and surgical nurses in the Chinese context. In this observational study, we used semi‐structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 57 publications
1
19
0
2
Order By: Relevance
“…We found nurses generally regarded risk assessment to be a top priority when planning and delivering PIP. This finding resonates with the findings of previous studies that risk assessment is the initial step to guide nurses to plan PIP (Hultin et al, 2021; Li et al, 2021). In our study, in addition to the use of a structured tool, nurses also consider their ‘clinical judgment’ during risk assessment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found nurses generally regarded risk assessment to be a top priority when planning and delivering PIP. This finding resonates with the findings of previous studies that risk assessment is the initial step to guide nurses to plan PIP (Hultin et al, 2021; Li et al, 2021). In our study, in addition to the use of a structured tool, nurses also consider their ‘clinical judgment’ during risk assessment.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have explored PIP care in China (Li et al, 2021;Liu et al, 2019). The compliance rate for repositioning was 90% with immobile patients in a cross-sectional study (Liu et al, 2019), much higher than that reported in Sweden (44.3%) (Baath et al, 2014) and Australia (66.4%) (Chaboyer et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 87%
See 2 more Smart Citations
“…In a recent, large-scale, 1-day point prevalence study, the prevalence of ICU-acquired pressure injuries was 16.2% in 1,117 ICUs in 90 countries worldwide [ 4 ]. Once these pressure injuries occur, they are difficult to cure and can prolong hospitalization stay, increase health care costs, cause complications such as infection and pain, and lower patient quality of life [ 5 7 ]. Recently, an increase in mortality has been reported in patients who had developed pressure injuries during ICU admission; the mortality rate increased even more in patients who had a higher stage of ulcer [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%